(3GdThQi hOhQgG GdJTQjYj (B: s (3OQGSI OSJhQjI ebGQfI Hjf GdfXGe GdeUQj hGdfXGe GdESdGej (B/ s - (3MSf YHOGdZfj T`ffs; (3YHOGdYRjR aJMj Sec (B: s; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb (B- (3LGeYI GdbGgQI,s, 2014)
(3gPg GdQSGdI JHMK aj eHOE GdThQi aj Gdabg GdESdGej heTQhYjJg ef fUhU GdbQBf hGdSfI, hJHMK hLhHgG Ydj hdj GdCeQ hEdRGegG dg(B. (3hJNdU Edi JQLjM hLhH GdThQi Ydj hdj GdCeQ, hCfgG edReI dg dG eMGdI(B. (3hJHJcQ eYjGQkG ZjQ eSHhb CSeJg(B: [ (3GdeYjGQ GdJhGRfj (B] (3jMSe NdGakG GSJeQ bQGHI Cda hCQHYeGFI YGe Hjf GdabgGA HTCfgG(B. (3ceG jTcd gPG GdeYjGQ fXGekG SjGSjkG LOjOkG jVGa Edi GdCfXeI GdSjGSjI GdKdGKI GdeYQhaI (B[ (3GdHQdeGfj hGdQFGSj hGdeLdSj (B]. (3Ke JYbO GdQSGdI aj gPG GdUOO ebGQfI Hjf GdGNJUGU GdJTQjYj ddThQi aj Gdabg GdESdGej hHjf GdGNJUGU GdJTQjYj GdPj efMg GdeTQY GdOSJhQj deLdS GdfhGH aj GdOSGJjQ GdeUQjI GdeJYGbHI OSJhQ(B1971 (3GdedZi, hOSJhQ GdKhQI GdLOjO(B2012, (3hhKjbI OSJhQ(B2014. (3hJhUj HVQhQI JYOjd GdfUhU GdOSJhQjI GdeNGdaI ddThQi GdESdGejI Ydi fSb eYjGQfG GdLOjO GdePchQBfakGs
2014. (3CWQhMI (B((3OcJhQGg(B)-s
(3HHdjhLQGajG(B: (3UaMGJ (B442-466.s
(3GdedNU HGddZI GdYQHjIs
Keywords: (3GdThQi aj GdfXGe GdSjGSj GdESdGej hGdeUQjs; (3COdI eTQhYjI GdThQi s; (3GdOjehbQGWjI s; (3Mce GdThQis; (3Cgd GdThQi s; (3eUGOQ GdJTQjY aj GdESdGe s; (3GdeLdS GdfjGHj GdeUQj heUGOQg ddJTQjY s; (3fXQjI GdVQhQI s; (3GdGNJUGU GdJTQjYj dQFjS GdLeghQjI s; (3GdThQi aj GdfXGe GdSjGSj GdESdGej hGdeUQjs